Meningothelial Hamartoma Overlying a Prior Craniotomy: A Case Report and Review of Literature - Unadkat, Prashin; Vitkovski, Taisia; Zaidi, Raza; Eisenberg, Mark (Asian Journal of Neurosurgery, 2022)
Meningothelial hamartomas are benign lesions of the scalp with a handful of case reports published. Usually thought to be congenital lesions, they have, on occasion, been seen in older adults. In this report, we describe the first ever reported case of a patient diagnosed with a meningothelial hamartoma overlying a prior craniotomy performed two decades prior. We also briefly describe the literature surrounding these rare lesions, as well as their management and differential diagnosis.
Keywords: meningothelial hamartoma; scalp tumor; craniotomy; Meningioma